Effectiveness Of Warm Compress on Dysmenorea in Adolescent Females at State Senior High School 1 Bonepantai - Meysil Musa; Raden Maria Veronika Widiatrilupi (NAJ Nursing Applied Journal, 2025)
Background: Dysmenorrhea, or menstrual pain, is a common health problem experienced by many adolescent girls worldwide. The prevalence of dysmenorrhea in Indonesia reaches 70%, significantly impacting adolescents' quality of life. This study aimed to explore the effectiveness of warm compresses as a method for managing dysmenorrhea pain among adolescent girls at SMA Negeri 1 Bonepantai. Objective: This study aims to measure the effect of using warm compresses on the level of dysmenorrhea pain in adolescent girls, as well as to provide insight into non-pharmacological methods that can be used as an alternative in dealing with this problem. Methods: This study used a pre-experimental design with one group pre- and post-test. The sample consisted of 35 tenth-grade female adolescents with dysmenorrhea, taken through purposive sampling. Initial data were collected using a visual analog scale (VAS) to measure pain levels before and after the warm compress intervention. Results: The analysis showed a significant decrease in pain levels after the application of warm compresses. The average pain score before the intervention was 7.5, while after the intervention it decreased to 3.2. The Wilcoxon Signed Rank Test showed a p-value of 0.000, indicating a significant difference between the pre-test and post-test scores. Conclusion: Warm compresses were proven effective in reducing dysmenorrhea pain in adolescent girls at SMA Negeri 1 Bonepantai. These findings demonstrate that simple interventions can have a positive impact on adolescent health and support the importance of further research into other methods of menstrual pain management.